Plan de proyecto para el marco de gobernanza de proyectos en una empresa desarrolladora de software, bajo buenas prácticas del PMI® - Guachamín Jacho, Luis Hernán (2019)
The present work, developed for Bupartech; company dedicated to the provision of financial solutions, aims to develop the Project Plan for the Software Project Governance Framework and propose a set of project management indicators aligned to its strategic objectives, which will be the input for the creation of a scorecard. The dynamism of the software industry, increasingly demanding customers, stakeholders that hope to complete their projects successfully and meet the expected benefits, make project management, despite having good practices such as those provided by the Project Management Institute, be managed by certified PMP® professionals and have methodologies; it needs the support of a higher authority known as Project Governance, which, through its processes and functions to supervise, control, integrate and make decisions, focuses on aligning governance with the organizational structure, identifying opportunities and threats to minimize risks and maximize results, measure and evaluate key performance indicators to add value to the business and manage communications so that it reaches all stakeholders and ensures organizational change. Therefore, project governance is a key tool to ensure success in project management since it can be adapted to any type and size of organization.